2022
DOI: 10.1007/s11356-021-17859-8
|View full text |Cite
|
Sign up to set email alerts
|

PPE pollution in the terrestrial and aquatic environment of the Chittagong city area associated with the COVID-19 pandemic and concomitant health implications

Abstract: The present study focuses on the indiscriminate disposal of personal protective equipment (PPEs) and resulting environmental contamination during the 3rd wave of COVID-19-driven global pandemic in the Chittagong metropolitan area, Bangladesh. Because of the very high rate of infection by the delta variant of this virus, the use of PPEs by the public is increased significantly to protect the ingestion/inhalation of respiratory droplets in the air. However, it is a matter of solicitude that general people throw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…7 shows the PPE footprints during this pandemic. Moreover, the Covid-19 driven PPE wastes are dumped into landfills without proper management because of the lack of available resources for PPE waste management ( Abedin et al, 2022 ). Once PPEs are dumped into the open environment, they react with air particles and turn as a source of exposure of contaminated air to the surrounding populace.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 shows the PPE footprints during this pandemic. Moreover, the Covid-19 driven PPE wastes are dumped into landfills without proper management because of the lack of available resources for PPE waste management ( Abedin et al, 2022 ). Once PPEs are dumped into the open environment, they react with air particles and turn as a source of exposure of contaminated air to the surrounding populace.…”
Section: Resultsmentioning
confidence: 99%
“…This fact shows the importance of proper strategies for handling and disposal of PPE wastes to avoid the extra route of transmission of the Covid-19 virus (WHO 2020). It has been reported that necessary financial support for proper protective strategies during the Covid-19 pandemic is absent in many low- and middle-income countries ( Abedin et al, 2022 ). Albeit, in the developed countries, the primary method for the disposal of infectious medical waste is incineration, followed by the landfilling with the residual ash ( Windfeld and Brooks, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…After use, they mostly end up in the environment (landfills, freshwaters or oceans), where the MP fibers continue to disintegrate into smaller pieces. Although several studies confirmed that PPEs were already present to varying degrees in the coastal zones from South America ( Thiel et al 2021 ; De la Torre et al 2021; Ardusso et al 2021 ) to Africa ( Okuku et al 2021 ), river outlets ( Cordova et al 2021 ), and urban environments ( Ryan et al, 2020 , Ammendolia et al, 2021 , Abedin et al, 2022 ); based on the fate of degrading surgical masks, it can be anticipated that excessive PPE use due to COVID-19 can significantly increase the amount of related MPs in the environment within a short period of time ( Fadare and Okoffo, 2020 , Pizarro-Ortega et al, 2022 ).…”
Section: Introductionmentioning
confidence: 97%
“…Since the declaration of the Covid-19 disease as a pandemic by the World Health Organization ( WHO, 2020 ), disposable personal protective equipment (PPE) has been adopted as an essential measure to prevent the spread of the infection. Several authors ( Abedin et al, 2022a ; Abedin et al, 2022b ; Akhbarizadeh et al, 2021b ; De-la-Torre and Aragaw, 2021 ; De-la-Torre et al, 2022b ; Rakib et al, 2021 ) have shown how the indiscriminate disposal of PPE wastes and their accumulation in beaches, coastlines, rivers, and littering cities can be a significant source of microplastics, although the magnitude of this contamination is still unknown. Face masks, the most abundant type of PPE, if exposed to environmental conditions, may be compromised in their fibrous structure, leading to rougher surfaces, cracks, ruptures, and releasing of microfibers.…”
Section: Introductionmentioning
confidence: 99%
“…The released microfibers become easily transportable to soil and/or marine environment with deleterious consequences ( Akhbarizadeh et al, 2021b ; Aragaw, 2020 ; De-la-Torre et al, 2022a ; De-la-Torre et al, 2022b ; De-la-Torre and Aragaw, 2021 ; Fadare and Okoffo, 2020 ; Rathinamoorthy and Balasaraswathi, 2022 ; Saliu et al, 2021 ; Shen et al, 2021 ; Wang et al, 2021 ). Masks release both high-density microplastics that may sink and reach the bottom sediments and low-density neustonic microplastics ( Abedin et al, 2022b ). Microplastics spread throughout the marine ecosystem and can be easily ingested by aquatic organisms and transferred through the trophic web to different trophic levels.…”
Section: Introductionmentioning
confidence: 99%